Encyclopedia of educational leadership and administration - English, Fenwick W. (Gale virtual reference library, 2006)
Presents the most recent theories, research, terms, concepts, ideas, and histories on educational leadership and school administration as it is taught in preparation programs and practiced in schools and colleges today. With over 600 entries, written by more than 200 professors, graduate students, practitioners, and association officials, the two volumes of this Encyclopedia represent a comprehensive knowledge base of educational leadership and school administration.